PENGARUH PENINGKATAN KOMPETENSI FIRST AID TERHADAP SELF AWARENESS RELAWAN BENCANA DI DESA DAYU KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Fahrudin, Havid; Wahyuni, Purbudi; Prasetya , Johan Danu (Indonesian Journal of Environment and Disaster, 2023)
The purpose of this study was to analyze the level of basic knowledge related to the competence of first aid volunteers, the effect of increasing first aid competence on volunteer self-awareness, and strategies for increasing self-awareness for disaster volunteers in Dayu Village, Gondangrejo District, Karanganyar Regency. This study employs a pre-experiment design with a one-group pretest and post-test method. The results of this study showed that basic knowledge related to first aid competence received a score of 80% for 24 volunteers, while the smallest percentage was for those who received a good score of 6.67% for 2 volunteers, and the rest were respondents who received a poor score of 13.33% for 4 volunteers. Other results, showed an increase in competence after the first aid training was carried out, the percentage of respondents with good scores reached 93.33%, for 28 respondents; and there was an increase in self-awareness after the first aid training was carried out, the percentage of respondents with good scores reached 86.66% for 26 respondents. Based on the results of the paired t-test, we obtained a p-value = 0.000 (p <  0.05), indicating that there was an effect of increasing first aid competence on the self-awareness of disaster volunteers in Dayu Village, Gondangrejo District, Karanganyar Regency. Furthermore, the strategies for increasing self-awareness can be carried out with training to increase competence that can influence controlling impulses, the ability to understand oneself, and the ability to be optimistic which can increase self-awareness. AGIL (Adaptation, Goal Attainment, Integration, Latency).